PUTRANJIVA- A HERB FOR PUMSAVANA (MALE PROGENY FACILITATOR)? - Vidhya, Unnikrishnan; Nishteswar, K. (International Journal of Ayurveda and Pharma Research, 2015)
Indian Community is obsessed to have at least one male child since ancient time. Pumsavana karma is a procedure performed in ancient India for achieving a progeny of desired sex. In the Samhitas herbs like Lakshmana, Vatasunga, Gouradanda apamarga, Jeevaka, Rshabhaka, Sairyeyaka are mentioned in various modalities for performing Pumsavana karma. Recently it has become a topic of discussion about Putrnjivas role in begetting male child. This review discusses the various activities of Putranjiva mentioned in the Ayurvedic classics, the reported modern scientific validations and attempted to focus about the role of the drug in Pumsavana procedure. Putranjiva has been experimentally evaluated for anti-inflammatory, antipyretic, antinociceptive, antioxidant, aphrodisiac, antimicrobial, hypoglycemic, and cytotoxic activites. Ayurvedic classics have not described male progeny promoting activity of Putranjiva, while ethno medicinal practices reported the usage of Putranjiva for begetting male child.